Bioceramic dip-coating on Ti-6Al-4V and 316L SS implant materials - Aksakal, Bunyamin; Hanyaloglu, C. (Springer, 2008)
The focus of the present study is based on more economical and rapid bioceramic coating on the most common implant substrates such as Ti-6Al-4V and 316L SS used often in orthopedics. For ceramic dip coating of implant substrates, Hydroxyapatite (HA) powder, Ca-10(PO4)(6)(OH)(2), P2O5, Na2CO3 and KH2PO4 are used to provide the gel. Ceramic films on sandblasted substrates have been deposited by using a newly manufactured dip-coating apparatus. Sample characterization is evaluated by SEM and XRD analysis. A smooth and homogeneous coating films have been obtained and average of 20 MPa bonding strength has been achieved for both Ti-6Al-4V and 316L SS alloys after sintering at 750 degrees C under flowing argon. The level of importance of the process parameters on coating was determined by using analysis of variance (ANOVA). The current process appears to be cheap, easy, and flexible to shape variations and high production rates for orthopedic applications.
Keywords: Hydroxyapatite Coatings; Gel; Composites; Films